(untitled) (World Bulletin of Management and Law, 2023)
This article examines the theoretical and legal aspects of correcting judicial errors in the realization of human rights. Focusing on key elements such as the presumption of innocence, appeal and cassation procedures, the application of international standards and legal accountability, the article analyzes the importance of correcting errors in judicial decisions. The article also emphasizes the need to respect universal human rights and ensure fairness in the judicial system. The importance of international norms in preventing judicial errors and establishing accountability mechanisms for them is discussed